On Vertically Challenged and Horizontal Equity : Reassessing Anti-Discrimination Rules - Efraim Sadka; Yoram Margalioth; Tomer Blumkin (Institute for the Study of Labor (IZA), 2004)
We consider a model of prejudice-driven discrimination, where the advantaged 'tall' discriminate against the disadvantaged 'short'. We employ an egalitarian social welfare function to compare anti-discrimination legal rules with a non-discriminatory ('height-blind') income tax.
Keywords: H2; D6; 330; discrimination; optimal taxation; horizontal equity; Arbeitsmarktdiskriminierung; Gleichberechtigung; Einkommensteuer; Optimale Besteuerung; Soziale Wohlfahrtsfunktion; Wohlfahrtseffekt; Theorie